Procedures for Senate Chair Survey On the State of Shared Governance On Their Campus, 2016 - 2017 - Salisbury University Faculty Senate (My University, 2016)
Procedures for Faculty Senate chair survey on the state of shared governance on their campus from 2016
Keywords: Shared Governance; Governance Consortium